Unpacking gender discrepancies in academic promotion across STEM fields in Mexico - Lauren Lanahan; Claudia Gonzalez-Brambila; Daniel Erian Armanios (PLoS ONE, 2025)
Gender inequality in the sciences remains a persistent issue. Women are often unable to participate in the scientific process as easily as men. When they do, this is largely constricted to opportunities at the lower rather than higher ranks of academia. This gap not only sets back female scientists but also scientific and social progress, more generally. The objective of this study is to look at a prominent national program for researchers in Mexico – Sistema Nacional de Investigadores (SNI) – to assess additional productivity and promotion heterogeneity by gender across career trajectories and disciplinary boundaries. Tracing productivity and promotion activity for 18,799 researchers active in the SNI program from 1991 to 2011, the analysis uncovers the following: while female researchers are associated with more productivity than males at each stage of the program, they are less likely to attain higher levels of promotion as they progress through their career. Illustratively, our more conservative results indicate women are associated with 1.2 more publications than men the year prior to promotion to Level 2 from Level 1 in SNI. Yet, 13 percent of women are associated with Level 2 promotion compared to 22 percent of men. To contextualize our understanding of these patterns, we interviewed SNI participants and include empirical assessments to unpack what may explain these perplexing results. While significant female representation in the applicant pool is needed to improve the gender gap, only a marginal increase in the gender representation of the reviewer pool is needed to reduce it significantly. This result points to a novel underexplored mechanism to inform future studies and policy – that of evaluative salience . While this does not fully address gender bias in the sciences, a shift in salience from applicants to reviewers may be an important precursor to address more structural ills around gender inequality.